(untitled) (Mūzikas akadēmijas raksti, 2024)
The musical set theory is a concept used for the characterization of the musical objects and their relationships. Not only is the set theory popular as a whole but also its separate elements, aspects and terms. Many of the basic axioms – sound set, intervallic vector, etc. – have been rooted in the western music theory so fundamentally, that are being used without special explanations and references to sound set theory as the first source. In the course of the article the historical development of the theory and its main developer Allen Forte is mentioned, whose work The Structures of Atonal Music (1977) is the most famous research of musical set theory. Today the set theory is used not only as a concept of musical analysis but also as an instrument for composing music. Several leading contemporary music composers – Magnus Lindberg, Hanspeter Kyburz and others – use the principles of the set theory in order to organize the parameters of harmony of their compositions.